2021
DOI: 10.14797/dpyf8504
|View full text |Cite
|
Sign up to set email alerts
|

Transcatheter Mitral Valve Repair for Severe, Symptomatic Mitral Regurgitation in Patients with Left Ventricular Assist Devices

Abstract: Patients with symptomatic stage D heart failure who require left ventricular assist device (LVAD) support and suffer concomitant severe mitral regurgitation are often difficult to manage. One reason is due to cardiac anatomic constraints that limit optimization of the mechanical assist device. Typically, these patients are not candidates for repeat sternotomy with surgical mitral valve repair, and heart transplantation may not be feasible or timely. This case describes two patients with LVAD support who receiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Some authors questioned whether the presence of >2 MitraClips -an uncommon event- could negatively affect LVAD therapy by: (i) affecting right ventricular function due to the presence of an inter-atrial shunt through the residual atrial septal defect and (ii) decreasing left ventricular filling and LVAD flow as a result of a reduced valve area combined with the increased flow rates after LVAD initiation ( 112 , 113 ). Raghunathan et al reported a case of bidirectional -predominantly right-to-left- shunting immediately after the delivery of two MitraClip XTR in an LVAD patient with right ventricular dysfunction ( 91 ). Percutaneous closure of the transseptal puncture with an Amplatzer occluder device led to symptomatic improvement of the patient's heart failure symptoms ( 91 ).…”
Section: Thv Interventionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some authors questioned whether the presence of >2 MitraClips -an uncommon event- could negatively affect LVAD therapy by: (i) affecting right ventricular function due to the presence of an inter-atrial shunt through the residual atrial septal defect and (ii) decreasing left ventricular filling and LVAD flow as a result of a reduced valve area combined with the increased flow rates after LVAD initiation ( 112 , 113 ). Raghunathan et al reported a case of bidirectional -predominantly right-to-left- shunting immediately after the delivery of two MitraClip XTR in an LVAD patient with right ventricular dysfunction ( 91 ). Percutaneous closure of the transseptal puncture with an Amplatzer occluder device led to symptomatic improvement of the patient's heart failure symptoms ( 91 ).…”
Section: Thv Interventionsmentioning
confidence: 99%
“…Raghunathan et al reported a case of bidirectional -predominantly right-to-left- shunting immediately after the delivery of two MitraClip XTR in an LVAD patient with right ventricular dysfunction ( 91 ). Percutaneous closure of the transseptal puncture with an Amplatzer occluder device led to symptomatic improvement of the patient's heart failure symptoms ( 91 ). Of note, less than 30% of patients have a residual iatrogenic atrial septal defect 1 year from MitraClip treatment ( 114 ).…”
Section: Thv Interventionsmentioning
confidence: 99%